2013
DOI: 10.1093/ndt/gft103
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease is associated with increased platelet activation and poor response to antiplatelet therapy

Abstract: Patients with CKD exhibit increased platelet activation, and an attenuated response to dual antiplatelet therapy compared with patients without renal insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
105
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 36 publications
4
105
0
Order By: Relevance
“…20,21 Previous studies have shown that patients with CKD exhibited significantly higher platelet activation and on-treatment residual ADP-inducible platelet reactivity than patients without renal insufficiency. 20,[22][23][24] Moreover, a low response to clopidogrel might be an independent predictor of the poorer outcomes in these CKD patients. Nowadays, the use of higher than usual clopidogrel doses (600 mg as loading dose and 150 mg as maintenance dose), 25 longer therapy duration (beyond 12 months), 26 or alternative more potent thienopyridine agents such as prasugrel 27,28 or ticagrelor 29 have been proposed as ways to overcome the clopidogrel resistance in CKD.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Previous studies have shown that patients with CKD exhibited significantly higher platelet activation and on-treatment residual ADP-inducible platelet reactivity than patients without renal insufficiency. 20,[22][23][24] Moreover, a low response to clopidogrel might be an independent predictor of the poorer outcomes in these CKD patients. Nowadays, the use of higher than usual clopidogrel doses (600 mg as loading dose and 150 mg as maintenance dose), 25 longer therapy duration (beyond 12 months), 26 or alternative more potent thienopyridine agents such as prasugrel 27,28 or ticagrelor 29 have been proposed as ways to overcome the clopidogrel resistance in CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Although several earlier reports have examined the association between renal impairment and platelet reactivity after PCI, results thus far have been inconsistent as previous studies were limited by modest sample sizes, inclusion of select cohorts, or lack of adequate multivariable adjustment. 14,16,17,24 In stable diabetic patients, for example, Angiolillo et al 24 previously demonstrated an independent association between CKD and HPR. Similarly, in a separate cohort involving 316 post-PCI patients with and without DM, Gremmel et al 16 also demonstrated a significant association between CKD and HPR using different assays.…”
Section: Discussionmentioning
confidence: 99%
“…14,16,17,24 In stable diabetic patients, for example, Angiolillo et al 24 previously demonstrated an independent association between CKD and HPR. Similarly, in a separate cohort involving 316 post-PCI patients with and without DM, Gremmel et al 16 also demonstrated a significant association between CKD and HPR using different assays. Our findings documenting a higher prevalence of HPR among those with versus without CKD, therefore, are largely confirmatory of these previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations